On Geometry of Volume Elements and Fractional Differentiable Manifolds: Wedad Salleh, Adem Kilicman - Team, Support (Thai Journal of Mathematics, 2020)
In this paper, the area and volume on fractional differentiable manifolds are discussed. Further, some examples are given.